Low Wages in Post-Communist EU Countries – The Case of the Czech Republic - Hornát, Filip; Potužák, Pavel; Miklánek, Tomáš; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
The paper examines the topic of low wages in post-communist countries with a special emphasis on the Czech Republic. Firstly, the paper presents the theoretical aspects of wage determinants and how they can affect wage differentials. Next, the paper studies wage convergence theoretically and also empirically on data showing that in the member states of EU that are also members of the OECD wage convergence is observed. In the next empirical section, using a unique individual dataset a model on wage determinants in the Czech Republic for the period 2004-2013 is estimated. The results show that the returns to a university degree have diminished and wage differentials between managerial and lower positions in the hierarchy have grown. Furthermore, the paper investigates individual wage determinants in the Czech Republic, Austria, Germany and Slovakia. The results show that the coefficients for these determinants differ significantly and may be reason or explanations for wage differentials between these countries. Despite the fact, that the structure and characteristics of the labor markets of these countries do not differ substantially.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses